On-site production of high-purity hydrogen from raw biogas with fixed-bed chemical looping. (15th September 2022) - Stoppacher, B.; Sterniczky, T.; Bock, S.; Hacker, V.
Highlights: First coupling of a 10 kW fixed-bed chemical looping system with a 3 MW biogas digester. Hydrogen purity of 99.998% without downstream purification from raw producer biogas. Quantification was proved by the carbon mass balance within a mean deviation of 9% Comparable process efficiency (2.9% deviation) related to synthetic biogas utilization. Abstract: Chemical Looping Hydrogen processes among others, show an outstanding potential for the decentralized conversion of biogas into high-purity hydrogen. For the first time, a 10 kWth fixed-bed chemical looping system has been coupled directly to a 3 MWth biogas digester in the southern region of Austria in the scope of the Austrian research project Biogas2 H2 . This experimental lab system resembles a blueprint for a potential future industrial system design. A comprehensive parameter study pointed out the influence of relevant process parameters (temperature, O/R ratio, reduction time, steam quantity in oxidation) on hydrogen purity and process efficiency. At the optimal operating point (850 °C, O/R 1.2), the process efficiency was comparable to the utilization of synthetic biogas in previous investigations within a deviation of 2.9%. Sulfuric compounds were isolated before entering the chemical looping system in order to avoid harmful contamination of the product hydrogen and performance loss, as investigated in preliminary experiments. The generated hydrogen was characterized online by ppm-range gas analysis and exhibited a product gas quality of up to 99.998%, with residual CO and CO2 as only contaminants. The fulfillment of the carbon mass balance within a mean deviation of 9% proved the correct quantification. The results indicate that coupling fixed-bed chemical looping systems to biogas plants enables the production of a fuel cell grade hydrogen and a sufficient process efficiency in upgrading local available biogenic and agricultural residuals to high-purity hydrogen.